Prevalence of HIV, Treponema pallidum and Their Coinfection in Men Who Have Sex with Men, Medellín-Colombia - Cardona-Arias JA; Vidales-Silva M; Ocampo-Ramírez A; Higuita-Gutiérrez LF; Cataño-Correa JC (HIV/AIDS: Research and Palliative Care, 2024)
Jaiberth Antonio Cardona-Arias,1 Mauricio Vidales-Silva,1 Alexandra Ocampo-Ramírez,1 Luis Felipe Higuita-Gutiérrez,1,2 Juan Carlos Cataño-Correa3 1Escuela de Microbiología, Universidad de Antioquia, Medellín, Colombia; 2Facultad de Medicina, Universidad Cooperativa de Colombia sede Medellín, Medellín, Colombia; 3Facultad de Medicina, Universidad de Antioquia, Fundación Antioqueña de Infectología, Medellín, ColombiaCorrespondence: Luis Felipe Higuita-Gutiérrez, Email hgfelipe87@gmail.comIntroduction: In Colombia, HIV and gestational syphilis are notifiable events; however, they are poorly investigated infections in men who have sex with men (MSM).Objective: To determine the prevalence of HIV, Treponema pallidum, and their co-infection in MSM treated at a Health Services Provider Institution (HSPI) specialized in infectious diseases from Medellín.Methods: Cross-sectional study with 3454 MSM. Prevalence was determined with its 95% confidence interval; associated factors were identified using Fisher’s Exact test, Pearson’s Chi-square, and trend Chi-square. Multivariate adjustment was performed using logistic regression. Analyses were performed using SPSS 29.0.Results: The prevalence of HIV was 5.7%, T. pallidum 0.7%, and co-infection 0.6%. The prevalence of HIV was higher in MSM aged between 24– 40 years (7.5%), with technical or university studies (10.0%), without health insurance affiliation (12.4%), and those who have had a sexual partner with HIV (36.2%). T. pallidum was higher in MSM without health insurance affiliation (3.4%), who had sexual relations with people diagnosed with an STI (5.9%), and a sexual partner with HIV (12.1%). Co-infection was higher in MSM without health insurance affiliation (2.7%), and those who had a partner with HIV (11.2%).Conclusion: Compared with the general Colombian population, MSM have a higher risk of HIV, but are similar to T. pallidum. The identification of the main associated factors in each infection demonstrates the need to prioritize subgroups of MSM that show greater vulnerability to these events. This research demonstrates the urgency of implementing health education strategies in MSM who have a sexual partner with HIV or other STIs. Large gaps were also evident in the magnitude of the three events according to the health insurance affiliation regime, which demonstrates problems of social and health injustice, especially with MSM without health insurance affiliation.Keywords: men who have sex with men, HIV, T. pallidum, syphilis, STI, coinfection, prevalence